The games [compact disc, unabridged] - Patterson, James, 1947-; Sullivan, Mark T. (Patterson, James, 1947- Private novels., 2016)
Two years after averting disaster while overseeing security for the World Cup, Jack Morgan, the head of international investigation firm Private, returns to Rio to secure the Olympics, only to confront a Brazilian saboteur who is hatching a lethal plot.